Cuban medical students’headache in relation to factors associated with academic stress - Annier Jesús Fajardo Quesada; María de los Ángeles Licea González; Fidel Jesús Moreno Cubela; Eduardo Adiel Landrove Escalona; Yudier Brizuela Fernández (Medisur)
Background: headache and stress can become quite common in the university students’ life. Therefore, it is necessary to study in depth the causes and consequences of this problem. Objective: to characterize the headache in Cuban medical students in relation to factors associated with academic stress. Methods: a descriptive cross-sectional study was carried out in 205 Cuban medical students during April and May 2022. The variables age, sex, academic year, presence of associated disease, frequency per week, average hours of sleep per day, frequency variation (during oral exams, written exams, medical shifts, high extracurricular demands, days off), average pain intensity, most frequent onset time, duration, most commonly used drugs, and use of pain-relieving drugs were studied. Results: the headache incidence was 91.2%, predominantly in the female sex (95.6%). Students reported a higher frequency (61%) in evening hours, as well as in situations of written exams (64.4%). On days off, the frequency decreased (67.3%). The academic year did not show a significant influence on the headache duration or intensity. The use of drugs was not always considered effective in treating pain. Dipyrone was referred to as the most used drug (47.8%). Conclusions: the factors associated with academic stress were related to the presence of headaches in Cuban medical students, and are the possible cause of its high incidence.